2016
DOI: 10.1108/h-04-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Does microcredit improve wellbeing? Evidence from Indonesia

Abstract: Purpose This study aims to investigate whether microcredit programme has a positive impact on productive poors. Several areas of investigation include clients’ borrowing behaviour, level of savings and before-and-after psychological well-being comparison. Design/methodology/approach A case-study survey of 398 clients of a microcredit programme run by a charity organisation in Jakarta, Indonesia, was conducted in 2012. Descriptive statistics and cross-tabulation analyses were then performed to show the variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Like most Asian developing states, the majority of the poor populace in Pakistan live in rural areas, and poverty remains one significant challenge to the society. Inability to acquire formal credit support has often been argued as a crucial constraint in expanding farmers' production, which mostly restrains farmers from improving their living conditions in Pakistan (Coleman, 1999;Gale & Collender, 2006;Rokhim, Sikatan, Wibisono Lubis, & Setyawan, 2016). The loan conditions established by formal financial institutions usually exclude the poor farmers who farm on the non-secured lands and possess little tangible assets that can be offered as collateral for formal loans.…”
Section: Introductionmentioning
confidence: 99%
“…Like most Asian developing states, the majority of the poor populace in Pakistan live in rural areas, and poverty remains one significant challenge to the society. Inability to acquire formal credit support has often been argued as a crucial constraint in expanding farmers' production, which mostly restrains farmers from improving their living conditions in Pakistan (Coleman, 1999;Gale & Collender, 2006;Rokhim, Sikatan, Wibisono Lubis, & Setyawan, 2016). The loan conditions established by formal financial institutions usually exclude the poor farmers who farm on the non-secured lands and possess little tangible assets that can be offered as collateral for formal loans.…”
Section: Introductionmentioning
confidence: 99%
“…Terengganu reported that most of the clients borrowed for two times. Meanwhile, in other regions such as Indonesia, Rokhim et al (2016) found that the highest borrowing frequency of the clients was between one to three times, while the remaining borrowed for four times or more. The results in Table 2 shows that most of the clients are first-time borrowers and have received the credit loans in 2016.…”
Section: Resultsmentioning
confidence: 96%
“…Findings from the above studies show that prior research has been inconclusive in establishing a clear pattern of long-term contribution of microcredit to its recipients (Pitt and Khandker, 1998;Kiiza and Pederson, 2006;Rokhim et al, 2016;Shiferaw et al, 2017). Furthermore, not many such studies have been undertaken that focus on gender disaggregated effects [3] of microcredit and capital accumulation; hence, this study fills this gap and shows the direct implication of policy changes that promote microcredit financing.…”
Section: Introductionmentioning
confidence: 82%